Successful management of sudden cardiac arrest in an adolescent with arrhythmogenic right ventricular cardiomyopathy - Murt, Begüm; Ramoğlu, Mehmet Gökhan; Baskovski, Emir; Altın, Timuçin; Kendirli, Tanıl; Uçar, Tayfun (The Turkish Journal of Pediatrics, 2025)
Background. Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a fatal, genetically transmitted cardiomyopathy that can cause unpredictable malignant life-threatening arrhythmias. Arrhythmias that may be hemodynamically insignificant in healthy persons, yet may be fatal in patients with cardiomyopathy and end-stage heart failure. Thus, urgent and prompt management of arrhythmias in these patients is essential to achieve favorable outcomes.Case Presentation. Here, we present a 13-year-old male who was referred to our institution with a prediagnosis of ARVC and had sudden cardiac arrest on the second day due to ventricular tachycardia / fibrillation. Successful extracorporeal cardiopulmonary resuscitation (E-CPR) was performed. A successful endo-epicardial ablation of ventricular tachycardia and implantable cardiac defibrillator insertion were performed under extracorporeal membrane oxygenation (ECMO) due to recurrent malignant ventricular arrhythmias. On the fourth day, he was weaned from ECMO without any sequelae. Although the patient did not experience any hemodynamically significant or sustained tachycardia after catheter ablation, he underwent a successful transplantation due to progressive heart failure.Conclusion. Appropriate and urgent management of life-threatening arrhythmias and when necessary high-quality resuscitation measures including E-CPR and a multidisciplinary coordinated approach is crucial in the management of patients with cardiomyopathy and end-stage heart failure.
Keywords: arrhythmogenic right ventricular cardiomyopathy; implantable cardiac defibrillator; ablation; transplantation